Brain Respiration, Stres, dan Romantic Relationship pada Dewasa Muda - Efnie Indrianie; Meta Dwijayanthy (Humanitas (Jurnal Psikologi), 2024)
This research aims to see how the effect of Brain Respiration in reducing stress related to Romantic Relationships in young adults. Quasi-experimental was used in this study, and participants were recruited using purposive sampling. Thirty young adults experiencing romantic relationship problems were involved in the study. The participants were divided into experimental and control groups using randomized control. To measure electrodermal activity (EDA) that reflects stress, this study used a biofeedback device. The statistical analysis used was the T-Test and Mann-Whitney. From this study, it was found that the degree of stress in young adults who received Brain Respiration decreased (T-count = 0,001 < 0,05). When compared with the control group, the reduction in the degree of stress in young adults in the experimental group was much lower (x̄ post-test experimental group = 2,8 < x̄ post-test control group 4,8). The conclusion is that Brain Respiration can reduce the degree of stress in young adults experiencing romance problems.